Pandemi Covid-19: Bagaimana motivasi siswa pada pembelajaran pendidikan jasmani dalam menggunakan e-learning? - Rifaldi; Gazali, Novri (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
At this time the education system in the world is disrupted by the Covid-19 outbreak. So that the learning system changes drastically from face-to-face learning to online home learning. The purpose of this study was to determine student motivation in learning physical education in using e-learning in class VIII students of SMP Negeri 12 Pekanbaru during the Covid-19 pandemic. The type of this research is descriptive. The sample in this study amounted to 32 people. The research instrument used was the Likert scale or using a questionnaire. The data analysis technique used is to calculate the level of motivation categories owned by students in learning using e-learning. Based on the results of the study, the conclusions in this study were obtained, namely: the motivation of students in learning physical education in using e-learning in class VIII students of SMP Negeri 12 Pekanbaru was included in the value range of 61-80% or in the strong category with a percentage of 77.93%.